2002
DOI: 10.1007/s00347-001-0562-0
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo-Messung des Temperaturverlaufs während der Phakoemulsifikation

Abstract: The new probe proved to be a practical device to monitor temperature in the anterior chamber during phacoemulsification. Up to now we did not encounter any critical degrees of temperature but it should be pointed out that a functional irrigation unit, the use of pulse mode or permanent ultrasonic output and in particular the type of viscoelastic material used are all important parameters influencing the rise of temperature during phacoemulsification. Further experience and results obtained with the new probe w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…18 A single US pulse can increase the temperature by 0.8 C when close to the phaco tip. 19 In the bevel-up technique, the phaco tip, and therefore the source of heat, are farther from the endothelial cells than in the bevel-down technique, and this decreases the chance of endothelial cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…18 A single US pulse can increase the temperature by 0.8 C when close to the phaco tip. 19 In the bevel-up technique, the phaco tip, and therefore the source of heat, are farther from the endothelial cells than in the bevel-down technique, and this decreases the chance of endothelial cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…measured moderate temperature changes inside the anterior chamber near the probe with surgically relevant system settings in this study. The highest measured maximum temperature rise with an amplitude setting of 50% pulsed was 1.1 C. Use of the cw mode with a 50% amplitude setting caused a maximum temperature increase between 1.03 C and 2.74 C. Heisler et al (2002) measured comparable temperature increases during 50 surgeries, but the reported temperature data are not statistically sound.…”
Section: Discussionmentioning
confidence: 45%
“…Heisler et al (2002) measured, with thermocouples, the temperature elevation inside the anterior chamber during 50 surgeries. The temperature rise was below 3 C after sonication in continuous wave mode for 0.3-4.7 s and less than 2 C in pulse mode.…”
Section: Introductionmentioning
confidence: 99%
“…Darüber hinaus wird immer wieder die mit der Erwärmung bei der Phakoemulsifikation verbundene thermische Belastung der Zellen als möglicher Schädigungsmechanismus genannt [11][12][13]. Untersuchungen zeigen, dass unter praxisüblichen Bedingungen nur moderate Temperatursteigerungen zu erwarten sind [14,15]. Demnach ist nicht mit einem Ansteigen der Temperatur auf ein Niveau oberhalb der Körperkerntemperatur zu rechnen.…”
unclassified